Roles for the Dorsal Striatum in Aversive Behavior - Stanley, Adrien T.; Lippiello, Pellegrino; Sulzer, David; Miniaci, Maria Concetta (Frontiers in Cellular Neuroscience, 2021)
The ability to identify and avoid environmental stimuli that signal danger is essential to survival. Our understanding of how the brain encodes aversive behaviors has been primarily focused on roles for the amygdala, hippocampus, pre-frontal cortex, ventral midbrain and ventral striatum. Relatively little attention has been paid to contributions from the dorsal striatum (DS) to aversive learning, despite its well-established role in stimulus-response learning. Here we review studies exploring the role of DS in aversive learning, including different roles for the dorsomedial and dorsolateral striatum in classical “fear conditioning” as well as innate and inhibitory avoidance behaviors. We outline how future investigation might determine specific contributions from DS subregions, cell types and connections that contribute to aversive behavior.